Analysis of teacher readiness transition from early childhood education to elementary school - Setiawan, Zulfikri Ari; Zumrotun, Erna (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2025)
This research aims to analyze teacher readiness in facilitating students' transition from Early Childhood Education (PAUD) to State Elementary School (SDN) 01 Bulu in Jepara Regency. The transition from PAUD to elementary school is an important phase that influences children's early development in formal education, and teacher readiness in this process is a crucial factor in supporting students' adaptation and learning readiness. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews and documentation studies. Data analysis was carried out interactively with steps for data reduction, data presentation and drawing conclusions. The research results show that teacher readiness in this transition still needs to be improved, especially in terms of pedagogical knowledge regarding the characteristics of early childhood, appropriate learning planning, and collaboration abilities between PAUD and elementary school teachers. Recommendations from this research include increasing training and workshops for teachers regarding learning techniques that support transitions, as well as collaborative efforts between educational institutions in optimizing student readiness in the early stages of basic education.